Physical Performance in Older Cohorts: A Comparison of 81-Year-Old Swedish Men and Women Born Twelve Years Apart—Results from the Swedish Study “Good Aging in Skåne” - Henrik Ekström; Sölve Elmståhl; Lena Sandin Wranker (Journal of Aging Research)
Introduction/Aim of the Study. One way of investigating health trends at the population level is to study the physical performance and functional ability in different birth cohorts. The information obtained can be used to predict illness, disability, and future needs for care. However, contradictory findings have been reported when comparing the physical performance of older adult birth cohorts. The aim of this study was to investigate whether the birth cohort is associated with the level of physical performance in 81-year-old men and women born twelve years apart. Materials and Methods. Birth cohorts of both sexes drawn from the Swedish study “Good Aging in Skåne” for the years 1920–22 and 1932–34 were compared. Walking, the step test, the chair stand test, and the handgrip strength test were used as proxies for the physical performance. The results were adjusted for lifestyle habits and common chronic geriatric diseases. Results. Both men and women in the later-born cohort walked more quickly and completed the chair stand test faster, and women were also quicker in the step test. No significant differences were found in the grip test, in either the male or female cohorts. Discussion. Normative reference values for physical tests of subjects of different ages can be misleading unless cohort effects are considered. Furthermore, age-related trajectories can also be misinterpreted if cohort effects are neglected which, in the longer perspective, could affect health care planning. Conclusion. Birth cohort effects should be considered when comparing walking speed, number of steps, chair stands, and the step test, in men and women of older age.